2022
DOI: 10.1039/d2nj03805f
|View full text |Cite
|
Sign up to set email alerts
|

Ratiometric optical thermometry based on a Dy3+, Eu3+ co-doped GdAl3(BO3)4 phosphor

Abstract: Rare earth doped phosphors have been extensively used as self-calibrated ratiometric thermometers for their contactless, noninvasive and high precision properties. However, the drawbacks of low relative sensitivity and signal discernability...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 53 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…The Huang–Rhys factor ( S ) value is very close to 1, indicating that the YGBO: 0.075Cr 3+ sample has a weak electron–phonon coupling strength. The calculated optical band gap from the DR spectrum of the YGBO host is 4.60 eV (Figure S4), which is higher than those reported in the literature for other borate hosts such as GdAl 3 (BO 3 ) 4 ( E g = 4.34 eV) . A larger band gap can effectively suppress the thermal ionization process and nonradiative process of Cr 3+ ions …”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…The Huang–Rhys factor ( S ) value is very close to 1, indicating that the YGBO: 0.075Cr 3+ sample has a weak electron–phonon coupling strength. The calculated optical band gap from the DR spectrum of the YGBO host is 4.60 eV (Figure S4), which is higher than those reported in the literature for other borate hosts such as GdAl 3 (BO 3 ) 4 ( E g = 4.34 eV) . A larger band gap can effectively suppress the thermal ionization process and nonradiative process of Cr 3+ ions …”
Section: Resultsmentioning
confidence: 70%
“…The calculated optical band gap from the DR spectrum of the YGBO host is 4.60 eV (Figure S4), which is higher than those reported in the literature for other borate hosts such as GdAl 3 (BO 3 ) 4 (E g = 4.34 eV). 50 A larger band gap can effectively suppress the thermal ionization process and nonradiative process of Cr 3+ ions. 51 Figure 4c demonstrates the measured temperature-dependent luminescence decay curves.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Thus, Dy 3+ and Eu 3+ co-doping is an effective method for the adjustment of luminescence properties. Up to now, Dy 3+ and Eu 3+ co-doped luminescence materials have been researched, for example BaLa-LiWO 6 :Dy 3+ /Eu 3+ , 23 La(PO 4 ):Dy 3+ , Eu 3+ , 24 Ca 3 MgSi 2 O 8 :Eu 3+ , Dy 3+ , 25 GdAl 3 (BO 3 ) 4 :Eu 3+ , Dy 3+ , 26 and Ca 2 KZn 2 (VO 4 ) 3 :Eu 3+ , Dy 3+ . 27 It can be found that the emission combination of Dy 3+ (blue and yellow light) and Eu 3+ (red-orange and red light) can be used to adjust and improve the luminescence properties of Dy 3+ and Eu 3+ codoped luminescence materials by changing the ratio between Dy 3+ and Eu 3+ ions.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16][17][18] Generally, the emission spectrum of Eu 3+ is attributed to the 5 D 0,1,2 -7 F J transitions ( J = 4, 3, 2, 1, and 0), and presents an intense red emission. [19][20][21][22][23][24][25] However, the parity-and spin-forbidden transitions during emission due to Eu 3+ 4f-4f absorption transitions result in a weak emission intensity under blue and near-UV (NUV) excitation. This makes them unsuitable for LED applications.…”
mentioning
confidence: 99%